PENGARUH KINERJA KEUANGAN TERHADAP PERUBAHAN LABA PADA BANK UMUM SYARIAH DI INDONESIA - Amarilis, Ulfa; Harianto, Syawal; Hamdani, Hamdani (Ekonis: Jurnal Ekonomi dan Bisnis, 2025)
Abstract: The change in profit at Islamic commercial banks is influenced by various financial performance indicators that reflect the bank’s ability to manage capital, financing risk, and operational efficiency. The Capital Adequacy Ratio (CAR) indicates the level of the bank’s capital adequacy, Non-Performing Financing (NPF) measures the risk of problematic financing, while the Operational Expense to Operational Income ratio (BOPO) reflects the efficiency of cost management. This study aims to analyze the effect of CAR, NPF, and BOPO on profit changes in Islamic commercial banks in Indonesia. The research method used is a quantitative approach with secondary data in the form of annual financial statements of Islamic commercial banks for the 2019–2024 period. Analysis was conducted using panel data regression to examine both the simultaneous and partial effects among variables, with the aid of statistical software, namely Eviews 13. The results show that CAR, NPF, and BOPO simultaneously have a significant effect on profit changes. Partially, CAR has no effect on profit changes, while NPF and BOPO have a negative and significant effect on profit changes. The coefficient of determination (R²) value of 0.47 indicates that 47% of the variation in profit changes can be explained by the three independent variables. This suggests that strengthening capital, reducing problematic financing, and improving operational efficiency are important strategies for Islamic commercial banks to maintain sustainable profit growth.Keywords: CAR, NPF, BOPO, Profit Changes.